In The Machine Room of Hotel Pro Forma - Voss Ilum, Tine (Peripeti, 2017)
Since 2011, Hotel Pro Forma has had eight to ten students every six months, as part of Atelier Hotel Pro Forma. Students who have a background in sound, light, visual arts, dramaturgy, architecture, and arts management. A course designed to inspire, develop, and reconsider contemporary art practises, as Hotel Pro Forma writes on its website. Trainees are part of the study room for future productions, where challenging questions and assignments are presented in the atelier. Once a month The Atelier invites the public to a lounge, an open house, where the daily research and the artistic experiments acquire body and form.